Phosphatic Clay for Agricultural Uses: Bibliography - Edward A. Hanlon; James A. Stricker; Julie Carson (EDIS)
This document can be used by growers, land owners, government agency staff members, and elected officials who wish to know more about phosphatic clay as a valuable resource of Florida. This bibliography is divided into sections based upon subject area. The contents of this EDIS document shall be updated in 2008 following the normal UF/IFAS three-year revision policy. This document is SL224 a fact sheet of the Soil and Water Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date: April 2005.